Peran Coretax Sebagai Inovasi Digital Pelaporan Pajak SPT Masa PPh 21 - Anggraeni, Nia; Susilowati, Endah (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
This study aims to examine the role of Coretax as a digital innovation in reporting the Periodic Tax Return (SPT Masa) for Income Tax Article 21 (PPh 21), which has been nationally implemented since 2025. Coretax is an integrated tax administration system developed by the Directorate General of Taxes to combine the processes of electronic withholding tax slip (e-Bupot) creation, tax return reporting, and tax payment into one efficient and accurate online platform. The system simplifies reporting procedures, accelerates administrative processes, and enhances taxpayer compliance through real-time data integration and automatic validation. However, the implementation of Coretax faces challenges such as technical issues, intensive training needs for staff at Tax Service Offices, and limited digital literacy among taxpayers, especially micro, small, and medium enterprises (MSMEs). This study provides an overview of Coretax’s contribution to supporting the digital transformation of Indonesia’s tax system while identifying obstacles that must be addressed to ensure optimal system performance.